Phenolic Compounds in Cork-Closed Bottle-Fermented Sparkling Wines - Minnaar, P.P.; Gerber, P.; Booyse, M.; Jolly, N. (South African Journal of Enology and Viticulture, 2021)
Bottle fermented sparkling wine in South Africa is known as Méthode Cap Classique which is based on the method used in France for Champagne. The use of cork, instead of a crown cap during the second fermentation in sparkling wine was investigated for its effect on the phenolic profile of wines. Phenolic acids susceptible to migration from cork into wine were studied in two-disc corks from three different commercial suppliers, coded as Cork A, Cork R and Cork C and a crown cap closure. Gallic, caftaric, caffeic and p-coumaric acids were quantified in all samples using a liquid chromatographic technique. Physicochemical parameters were also measured in the wine using a spectrophotometric technique. Total acidity and pH were not significantly different among the wines. Cork R wines were however significantly different in alcohol. Residual sugar for all samples was below the limit of detection. Gallic acid was significantly highest in Cork A wines, which indicates the contribution of Cork A to the concentration of this compound in the wine. Different cork types are assumed to release different concentrations of phenolic compounds. This may be due to differences in surface roughness of cork that would increase the surface area in contact with the wine. Therefore, corks from different origins (suppliers) could be used to bring about subtle differences to the wine.